Finite element modelling and updating of welded thin-walled beam - Mohd Sahril, Mohd Fouzi; Khaironi, Mohd Jelani; N. A., Nazri; M. S. M., Sani (Universiti Malaysia Pahang, 2018)
This article concentrates on the finite element (FE) modelling approach to model welded thin-walled beam and the adoption of model updating technique to enhance the dynamic characteristic of the FE model. Four different types of element connectors which are RBE2, CBAR, CBEAM and CELAS format are used to construct the FE model of welded structure. Normal mode analysis is performed using finite element analysis (FEA) software, MSC Patran/Nastran to extract the modal parameters (natural frequency and mode shape) of the FE model. The precision of predicted modal parameters obtained from the four models of welded structure are compared with the measured counterparts. The dynamic characteristics of a measured counterpart is obtained through experimental modal analysis (EMA) using impact hammer method with roving accelerometer under free-free boundary conditions. In correlation process, the CBAR model has been selected for updating purposes due to its accuracy in prediction with measured counterparts and contains updating parameters compared to the others. Ahead of the updating process, sensitivity analysis is made to select the most sensitive parameter for updating purpose. Optimization algorithm in MSC Nastran is used in FE model updating process. As a result, the discrepancy between EMA and FEA is managed to be reduced. It shows the percentage of error for updated CBAR model shrinks from 7.85 % to 2.07 % when compared with measured counterpart. Hence, it is found that using FE model updating process provides an efficient and systemic way to perform a feasible FE model in replicating the real structure.